High-Affinity Ligands Can Trigger T Cell Receptor Signaling Without CD45 Segregation - Al-Aghbar, Mohammad Ameen; Chu, Yeh-Shiu; Chen, Bing-Mae; Roffler, Steve R. (Frontiers in Immunology, 2018)
How T cell receptors (TCR) are triggered to start signaling is still not fully understood. It has been proposed that segregation of the large membrane tyrosine phosphatase CD45 from engaged TCRs initiates signaling by favoring phosphorylation of immuno-receptor tyrosine-based activation motifs (ITAMs) in the cytoplasmic domains of CD3 molecules. However, whether CD45 segregation is important to initiate triggering is still uncertain. We examined CD45 segregation from TCRs engaged to anti-CD3 scFv with high or low affinity and with defined molecular lengths on glass-supported lipid bilayers using TIRF microscopy. Both short and elongated high-affinity anti-CD3 scFv effectively induced similar calcium mobilization, Zap70 phosphorylation and cytokine secretion in Jurkat T cells but CD45 segregated from activated TCR microclusters significantly less for elongated versus short anti-CD3 ligands. In addition, at early times, triggering cells with both high and low affinity elongated anti-CD3 scFv resulted in similar degrees of CD3 colocalization with CD45, but only the high affinity scFv induced T cell activation. The lack of correlation between CD45 segregation and early markers of T cell activation suggests that segregation of CD45 from engaged TCRs is not mandatory for initial triggering of TCR signaling by elongated high affinity ligands.